Category creation : how to build a brand that customers, employees, and investors will love - Kennada, Anthony, 1986- (Wiley, 2020)
"Salesforce, Hubspot, Gainsight, and other tech brands have pioneered a new marketing and branding playbook focused on serving the people *behind* the companies they sell to. They have built category-defining (and in some cases category-creating) companies and communities that led to faster growth, higher valuations, and dominant market positions. This book is an exclusive look into the 'human first' marketing playbook of some of the best brands in B2B, written for a new generation of entrepreneurs and marketers in companies of all sizes and stages of maturity. The book will document the rise, fall and return of B2B brand marketing, offer ten principles to building a modern B2B brand, and prove the value of brand marketing on shareholder outcomes"--